Mechanism of the connection between sacred and secular space: settlement morphology characteristics in the multi-ethnic areas of the Gansu-Qinghai Plateau - Jiang, Baolong; Jiang, Tao; Si, Jingyi; Huang, Yuhao; Du, Yuxuan; Chen, Yile (Frontiers in Earth Science, 2025)
Settlements in the Multi-ethnic Areas (SiMAs) of the Gansu-Qinghai Plateau reflect the long-term coordinated adaptation of rugged terrain, diverse ethnic cultures, and sacred beliefs, but rapid urbanization and secularization are threatening their spatial integrity. Based on a framework of 10 morphological indicators, this study conducted Principal Component Analysis (PCA) and Agglomerative Hierarchical Clustering analysis on 51 locals SiMAs to reveal the underlying spatial patterns. The results show that (1) four key factors—morphological cognition, structural order, traffic layout, and boundary shaping—greatly help explain the shape of SiMAs, accounting for 78.549% of the total variation. (2) This study identified five typical settlement space paradigms and listed six typical examples to support them. Ethnic settlements under different geographical environments and sacred beliefs have formed adaptive layouts with significant morphological differences. (3) Comparing different cases shows that sacred space, as a fundamental organizing idea, goes beyond ethnic differences to influence how settlements are arranged, while secular space changes and adapts based on various factors. The “spatial organization paradigm” proposed in this study clarifies how nature, culture, and functional drivers interweave to shape plateau settlements and provides a transferable practical path for community participation in conservation and sustainable planning of multi-ethnic mountain heritage sites around the world.